2012
DOI: 10.3109/08923973.2012.734511
|View full text |Cite
|
Sign up to set email alerts
|

Allergic colitis in monozygotic preterm twins

Abstract: Allergic colitis (AC) typically develops in the first weeks or months of life and is characterized by the presence of red blood in the stools of healthy breastfed or formula fed infants. In this paper, we describe a case of rectal bleeding in monozygotic preterm twins that was resolved with the introduction of a cow's milk protein-free diet (CMPFD). The occurrence of this disorder in monozygotic twins raises the question as to whether the underlying abnormality in the immune regulation, which leads to poor acq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…It is known that the gastrointestinal microbiota are transferred from mother to the baby and this may explain why the disease develops in siblings, especially twins 20 . Coviello et al 1 and Baldassarre et al 4 have also reported monozygotic infants who were diagnosed and treated as CMPA as in our case series.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…It is known that the gastrointestinal microbiota are transferred from mother to the baby and this may explain why the disease develops in siblings, especially twins 20 . Coviello et al 1 and Baldassarre et al 4 have also reported monozygotic infants who were diagnosed and treated as CMPA as in our case series.…”
Section: Discussionmentioning
confidence: 67%
“…One of the interesting features of our case series was that there were monozygotic triples and two were diagnosed with CMPA. This may be due to an inherited immune regulation abnormality, leading to poor tolerance 4 . Another possibility is the microbiota which was transferred largely through the gastrointestinal tract and the vagina of the mother to the infants during delivery 19 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Infants fed milk other than breast milk had four times the risk of MRB (odds ratio = 4.11 [95% CI = 2.41, 6.99]) [5]. It suggest that a possible relationship between rectal bleeding and intolerance to cow’s milk proteins which has been reported in preterm infants [15]. In our study, the type of milk at the time of rectal bleeding did not appear to be a risk factor, probably because feeding practices changed since the previous study performed in infants born between 1996 and 2001 [6].…”
Section: Discussionmentioning
confidence: 99%